Effective Disciplinary Strategies to Combating Indiscipline in Public Senior High Schools in Kumasi, Ghana - Kumah, Paul Kwasi; Dapaah, Jonathan Mensah; Dwumah, Peter; Hubert, Bimpeh Asiedu; Addai, Isaac (Journal of Education and Practice, 2023)
Purpose: The effective ways of handling misbehaviour in school is rarely deliberated upon by policy makers and educators. This research studied the effective strategies used in Public Senior High Schools in the Kumasi Metropolis of Ghana. Methodology: The mixed-method approach was used to gather both qualitative and quantitative data with structured questionnaires and interview guides. Findings: The analysis suggests that 92.21% of parents favoured suspension over rewards (9.03%). Teachers (86.74%) favoured referring students to the disciplinary committee over writing bad comments on students' reports (34.8%). Students (86.13%) preferred use of reward to caning (57.07%) as most effective disciplinary strategy. The analysis of variance (ANOVA) further suggested a significant difference in the perspective of parents, teachers and students on the most effective disciplinary strategies like rewards (P≤0.001), inviting parents (P≤0.000), negative testimonials (P≤0.000), suspension (P≤0.000), disciplinary committee (P≤0.000), manual work (P≤0.000), and caning (P≤0.000). The managers support the use of counselling, cleaning, weeding, reflection and repeating a class as effective. Unique Contribution to theory and practice: This study concludes with the proposition that disciplinary committee processes, suspensions and rewards for students are effective in handling student misbehaviour. It is recommended that parents, teachers, students and managers work together as collaborators in ensuring effective discipline in the school.